2006
DOI: 10.1007/s10565-006-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diazinon on lipid peroxidation and antioxidant enzymes in rat heart and ameliorating role of vitamin E and vitamin C

Abstract: Diazinon is one of the most widely used organophosphate insecticides (OPIs) in agriculture and public health programs. Reactive oxygen species (ROS) caused by OPIs may be involved in the toxicity of various pesticides. The aim of this study was to investigate how diazinon affects lipid peroxidation (LPO) and the antioxidant defense system in vivo and the possible ameliorating role of vitamins E and C. For this purpose, experiments were done to study the effects of DI on LPO and the activities of superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 27 publications
7
49
0
Order By: Relevance
“…This enzyme is sensitive to liver toxicity and its histopathological changes compared with other enzymes as ALP and AST that can be evaluated in a shorter period of time [32]. Another enzyme which is assessed to diagnose liver damage is ALP which exists in most tissues and its level is altered due to liver diseases [33]. ALT and ALP levels were increased significantly (p<0.05) in the current study after deltamethrin intoxication when compared with the control group.…”
Section: (Handex1000) C: Liver Tissue Section Of Rats Treated With Delmentioning
confidence: 53%
“…This enzyme is sensitive to liver toxicity and its histopathological changes compared with other enzymes as ALP and AST that can be evaluated in a shorter period of time [32]. Another enzyme which is assessed to diagnose liver damage is ALP which exists in most tissues and its level is altered due to liver diseases [33]. ALT and ALP levels were increased significantly (p<0.05) in the current study after deltamethrin intoxication when compared with the control group.…”
Section: (Handex1000) C: Liver Tissue Section Of Rats Treated With Delmentioning
confidence: 53%
“…Sahin et al [36] showed that erdosteine treatment in vancomycin-induced liver damage causes significant decrease in SOD, CAT, and GSH-Px activities. Akturk et al [37] studied the effects of diazinon on lipid peroxidation and antioxidant enzymes in rat heart and ameliorating role of VCE administration. They reported that VCE treatment led to decrease in SOD and CAT activities in diazinon-induced damage of rat heart [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that the increased activity of CAT is due to the adaptive response to the generated free radicals, indicating the failure of the total antioxidant defense mechanism to protect the tissues from mechanical damage caused by pesticides, as evidenced by lipid peroxidation (12)(13)(14). Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C treatment prevented the enhancement of SOD enzyme activities and enhanced the level of glutathione. Akturk et al (12) studied the effects of diazinon on lipid peroxidation and antioxidant enzymes in rat heart and the ameliorating roles of vitamin E and vitamin C. Their study found that vitamin E and C treatments led to diminished SOD and CAT activities in diazinon-induced damage of rat heart.…”
Section: Alveolar Edema and Congestionmentioning
confidence: 99%